2017
DOI: 10.1177/0276236617734787
|View full text |Cite
|
Sign up to set email alerts
|

Fantasy as a Driving Force: Relations Between Fantasy and Motivation in Children

Abstract: The relationship between children's fantasy involvement and motivational style at school was investigated. Participants were 95 Swedish children in third to fifth grade (9-11 years). Fantasy involvement was measured with the Children's Fantasy Inventory and motivation in the classroom was measured with the Goal Orientation Scales. Results revealed that being highly imaginative was related to higher mastery goal orientation. Among the two subscales with positive fantasy content, one-fanciful and happy fantasies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In a number of recent studies, neuroticism has been shown to predict higher emotional reactivity and reinforcement of negative fantasies, even when boredom is present (Caci et al., 2020). Negative fantasies are associated with avoidance goals and positive fantasies are associated with approach goals in school (Hoff et al., 2019). These goal orientations (approach versus avoidance) might also be relevant in relation to boredom (Nett et al., 2010, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of recent studies, neuroticism has been shown to predict higher emotional reactivity and reinforcement of negative fantasies, even when boredom is present (Caci et al., 2020). Negative fantasies are associated with avoidance goals and positive fantasies are associated with approach goals in school (Hoff et al., 2019). These goal orientations (approach versus avoidance) might also be relevant in relation to boredom (Nett et al., 2010, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such a prospective approach may help to inform the value and importance of childhood fantasy play at a time when this is increasingly being challenged (Russ, 2016). Specific applications of the RCFPS may involve studies considering the relationships between childhood fantasy predisposition and later socioemotional skills (e.g., theory of mind), personality traits (e.g., openness to experience, motivation, see Hoff, Ekmann, & Kemdal Pho, 2017 for a recent study), creativity and divergent thinking, and lifestyle or occupational functioning (e.g., artistic interest, career choice, and progression). While the RCFPS is not designed to have a clinically differentiating function, investigating the relationships between this measure and psychopathological traits that involve a reduced or increased interest in fantasy (e.g., autism and schizotypy; Crespi et al, 2016) would be of theoretical interest and provide further information about the psychometric properties of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fantasy serves as a driving force that helps people to maintain motivation (Klinger, 2013; Smallwood, 2010). A recent study (Hoff, Ekman, & Kemdal Pho, 2019), for example, investigated the relationship between children’s involvement in fantasy and motivational style at school, showing that fantasy involvement may be a resource for motivating students—that is, children’s interest in elaborating daydreams and imaginary play appears to predict their desire to explore and learn about the external word.…”
Section: Recent Empirical Findings On Fantasymentioning
confidence: 99%